Study of the impact of foundation settlement on the wind-induced vibration response of the transmission tower-line system - DING Xiang; XIA Haoyan; GONG Jiangang; ZHOU Qi; CAO Meigen (Zhejiang dianli, 2023)
Transmission towers are highly flexible and wind-sensitive structures. Uneven settlement of foundations followed by typhoons jeopardizes the operation safety of transmission towers. In order to assess the influence of foundation settlement on the wind resistance capacity of transmission towers， a coupled finite element model of the transmission tower-line system is established to compare and analyze the change law of wind-induced vibration responses， wind vibration coefficients and main material stresses of the transmission tower-line system under different tilt angles of foundation in case of a typhoon. The study shows that under the same tilt angle， the root mean square （RMS） of wind-induced vibration response increases significantly in the horizontal tilt in relation to vertical tilt by at most 40%； the structural tilt caused by the foundation settlement will lead to the wind vibration coefficient exceeding the specified value， and the most unfavorable situation will lead to the wind vibration coefficient exceeding the specified value by 9.6%； the change law of compressive stress is consistent with that of wind vibration coefficient， and the compressive stress increases most under a tilt angle of 5°， and the compressive stress increases by 16.1% in contrast to when the tower leg is not tilted. The research results have significant reference value for the wind resistance assessment and safe operation of transmission towers in typhoon-prone areas.